1998
DOI: 10.1038/sj.onc.1202147
|View full text |Cite
|
Sign up to set email alerts
|

Human lymphoblastoid cell lines expressing mutant p53 exhibit decreased sensitivity to cisplatin-induced cytotoxicity

Abstract: Human lymphoblastoid cells were transfected with expression vectors containing p53 cDNA mutated at either codon 135 or 246. The cells were subjected to cisplatin treatment or g-radiation and observed for changes in the cell cycle arrest and apoptosis. We found that compared to the parental cell line, cells overexpressing mutant p53 (either 246 val or 135 ser ) exhibited decreased apoptosis in response to g-radiation or cisplatin as measured by: propidium iodide (PI) staining of the cellular DNA (cell cycle ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…It has been widely demonstrated that cancer cells expressing mutated p53 are associated with an increased resistance to cisplatin and that expression of wt-p53 in these cells increased the cytotoxicity of cisplatin [21][22][23][24]. The present result shows that infection of Ad-PKC‰ alone could not induce MKN28 cell death effectively because a mutated form of p53 protein in MKN28 possibly plays a role as a dominant negative form [25]. Moreover, several other signaling components, e.g.…”
Section: Discussionmentioning
confidence: 56%
“…It has been widely demonstrated that cancer cells expressing mutated p53 are associated with an increased resistance to cisplatin and that expression of wt-p53 in these cells increased the cytotoxicity of cisplatin [21][22][23][24]. The present result shows that infection of Ad-PKC‰ alone could not induce MKN28 cell death effectively because a mutated form of p53 protein in MKN28 possibly plays a role as a dominant negative form [25]. Moreover, several other signaling components, e.g.…”
Section: Discussionmentioning
confidence: 56%
“…Among the main factors influencing cell sensitivity to cisplatin and oxaliplatin, those affecting the p53-dependent apoptotic pathway seem to be relevant [Gallagher et al, 1997;Piovesan et al, 1998;Manic et al, 2003]. Since CHO-K1 cells have a nonfunctional p53 protein [Hu et al, 1999], the tolerance of CHO-K1 cells to oxaliplatin may be related to an impairment of p53-mediated apoptosis.…”
Section: Cytotoxicity and Mutant Frequencymentioning
confidence: 95%
“…Inactivation of p53 contributes not only to tumor progression but also to resistance of cancer cells to chemotherapy (Fan et al, 1994;Goto et al, 1998;Piovesan et al, 1998), although certain exceptions have been described (Gudas et al, 1996). Moreover, restoration of wt p53 in cells lacking or expressing mutated p53 can enhance apoptosis induced by DNAdamaging agents or chemotherapy (Blagosklonny and El Deiry, 1998;Fujiwara et al, 1994;Gurnani et al, 1999;Ju et al, 1998;Seth et al, 1997;Song et al, 1997).…”
Section: Introductionmentioning
confidence: 99%